2024
DOI: 10.1021/acs.energyfuels.3c04835
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Membrane Development for High Temperature Proton Exchange Membrane Fuel Cells

Jiadi Ying,
Tiancun Liu,
Yeqing Wang
et al.

Abstract: High temperature proton exchange membrane fuel cells (HT-PEMFCs) are a promising energy conversion technology due to their quick reaction kinetics, high tolerance to CO impurities, and ease of heat and water management. Nevertheless, the practical implementation of this technology is limited since traditional proton exchange membranes (PEMs) exhibit significantly reduced performance at high temperatures and low humidity. In this extreme situation, researchers have concentrated on investigating new membranes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 180 publications
(264 reference statements)
0
0
0
Order By: Relevance
“…The main disadvantage of LT-PEMFCs is their need for pure hydrogen due to the sensitivity of Pt catalyst to hydrogen contamination . IT-PEMFCs and HT-PEMFCs have many pros than LT-PEMFCs, such as easier heat and water management, faster electrochemical reactions, lower costs of the MEA, and the added benefit of more tolerance to toxic carbon monoxide (CO). It has been found that small traces of CO (10–20 ppm) in the H 2 feed significantly lowered the LT-PEMFC performance. Contrary, the CO tolerance of the Pt catalyst can further boost up to 1000 and 10000 ppm when operated at high temperatures of 130 and 150 °C, respectively .…”
Section: Proton Exchange Membrane Fuel Cell (Pemfc)mentioning
confidence: 99%
“…The main disadvantage of LT-PEMFCs is their need for pure hydrogen due to the sensitivity of Pt catalyst to hydrogen contamination . IT-PEMFCs and HT-PEMFCs have many pros than LT-PEMFCs, such as easier heat and water management, faster electrochemical reactions, lower costs of the MEA, and the added benefit of more tolerance to toxic carbon monoxide (CO). It has been found that small traces of CO (10–20 ppm) in the H 2 feed significantly lowered the LT-PEMFC performance. Contrary, the CO tolerance of the Pt catalyst can further boost up to 1000 and 10000 ppm when operated at high temperatures of 130 and 150 °C, respectively .…”
Section: Proton Exchange Membrane Fuel Cell (Pemfc)mentioning
confidence: 99%